SOCIAL FACTORS INFLUENCING THE LIFESTYLE OF YOUNG PEOPLE - Atakulov Mavlonbek Saitkulovich (Western European Studies, 2025)
In this article, the adaptation of young people to the process of socialisation in society, the concepts of modern lifestyle, and the attitudes of the younger generation towards our national values are discussed. It is also noted that economic conditions, the family, education, and the system of national culture and values are closely interconnected as a sociophilosophical phenomenon that shapes young people’s attitudes towards their lifestyle. Furthermore, achieving an ideal level of youth health and lifestyle is presented as an indispensable stage in the implementation of any reform that a society seeks to carry out.
Keywords: youth; lifestyle; social factors; cultural values